Impact of Active Recovery and Whole-Body Electromyostimulation on Blood-Flow and Blood Lactate Removal in Healthy People - Sañudo, Borja; Bartolomé, Diego; Tejero, Sergio; Ponce-González, Jesús Gustavo; Loza, Juan Pedro; Figueroa, Arturo (Frontiers in Physiology, 2020)
This study aimed to determine whether an active recovery with added whole-body electromyostimulation (WB-EMS) can increase blood flow and lead to blood lactate removal after intense exercise. Thirty-five healthy individuals (23.1 ± 4.6 years) were randomly assigned to: (a) an experimental group using active recovery together with the WB-EMS (n = 18) or (b) a control group using the same active recovery protocol with the suit with no-stimulation (CON, n = 17). Participants performed a maximal graded exercise test followed by an active recovery protocol (walking at 40% of their maximum aerobic velocity). During the recovery, participants in WB-EMS and CON received continuous stimulation at 7 Hz or no stimulation, respectively. Heart rate, blood lactate concentrations, pain/discomfort, and hemodynamic measurements were recorded before and after the test, and repeated immediately after and at min 30 and 60. The between-group analysis showed a substantially greater Peak blood velocity (−0.27 [−0.68; 0.14]) in WB-EMS compared to CON. The pain/discomfort levels were also lower in WB-EMS compared with CON (0.66 [−0.12; 1.45]). Non-significant differences in participants’ blood lactate were observed in WB-EMS compared with CON both immediately; at 30and 60 min. Our findings suggest that increased local blood flow induced by WB-EMS may have contributed to greater lactate removal from active muscles and blood lactate clearance. WB-EMS may be an effective means of increasing muscle blood flow after a maximal graded exercise test and could result in improved recovery.